TRANSFORMASI PENJENAMAAN KOTA JAKARTA KOTA KOLABORASI MENJADI SUKSES JAKARTA UNTUK INDONESIA SEBAGAI IDENTITAS KOTA JAKARTA - Adityo Nugroho; Dewi Noor Azijah; Kariena Febriantin (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2026)
City branding is one way for local governments to increase regional competitiveness and potential, whereby branding originates from marketing science that is implemented in government science. Jakarta, as one of the major cities in Indonesia, has two city brands established by the Provincial Government of DKI Jakarta, namely +Jakarta a city of collaboration, for 2020-2022 and Sukses Jakarta Untuk Indonesia for 2022-2025. This study aims to determine the perceptions or views of the people of Jakarta regarding the two city brands of Jakarta, namely +Jakarta a city of collaboration and Sukses Jakarta Untuk Indonesia. Using a qualitative method with a phenomenological approach, data was collected through interviews, observations, and literature studies, with informants determined using purposive sampling. The results of the study show that the people of Jakarta prefer +Jakarta a city of collaboration as the identity of the city of Jakarta in terms of attributes, messages, differentiation, and ambassadorship compared to Sukses Jakarta Untuk Indonesia.